PENGARUH COLLEGE ADJUSTMENT PADA FENOMENA IMPOSTER SYNDROME DI KALANGAN MAHASISWA FAKULTAS ILMU PENDIDIKAN DAN PSIKOLOGI UNIVERSITAS NEGERI MANADO - Aurika Suak, Cherren; Hilda Mandang, Jofie; Angelina Kelly Lovihan, Mike; Reinie Undap, Tiersa (Penerbit Lafadz Jaya, 2025)
Imposter syndrome is a mental state marked by self-doubt and feelings of inadequacy about one's accomplishments, commonly encountered by students when navigating the academic, social, emotional, and institutional challenges of college life. The ability to adjust to college, known as college adjustment, is deemed a crucial element that can influence the occurrence of this condition. This research seeks to investigate how college adjustment impacts the experience of imposter syndrome among students in the Faculty of Education and Psychology at Manado State University. Employing a quantitative approach, this study uses simple linear regression analysis. The study involves 245 active students from the Faculty of Education and Psychology, selected through incidental sampling which means respondents were chosen based on their availability and willingness during data collection. The research tools include a college adjustment scale assessing academic, social, personal emotional, and institutional adaptation, alongside an imposter syndrome scale evaluating self-doubt, attributing success to luck, and the tendency to minimize achievements. The data analysis methods consist of prerequisite tests and hypothesis testing via simple linear regression analysis. Findings indicate that hypothesis H1 is supported, revealing a significant impact of college adjustment on imposter syndrome with a significance level of 0.001 (p = 0.001) and a regression coefficient of -0.224 (β = -0.224), signifying a negative and significant influence of college adjustment on imposter syndrome. The determination coefficient is 0.052, suggesting that the college adjustment variable accounts for 5.2% of the variations in imposter syndrome. Consequently, these outcomes demonstrate that the better students are able to adjust to college, the less likely they are to experience imposter syndrome, and vice versa.